Processing of voided urine for prostate cancer RNA biomarker analysis. Issue 16 (26th August 2015) - Quek, Sue‐Ing; Wong, Olivia M.; Chen, Adeline; Borges, Gisely T.; Ellis, William J.; Salvanha, Diego M.; Vêncio, Ricardo Z.N.; Weaver, Brandi; Ench, Yasmin M.; Leach, Robin J.; Thompson, Ian M.; Liu, Alvin Y.
<x xml:space="preserve">Abstract</x> BACKGROUND Voided urine samples have been shown to contain cells released from prostate tumors. Could good quality RNA from cells in urine be obtained from every donor for multimarker analysis? In addition, could urine donation be as simple as possible, a practical consideration for a lab test, without involving a prostate massage (as indicated for PCA3 testing), which precludes frequent collection; needing it done at a specific time of day (e.g., first or second urine); and requiring prompt processing of samples in clinics with limited molecular biology capability? METHODS Collected urine samples were pelleted, and the RNA isolated was processed for cDNA synthesis and in vitro transcription to generate amplified sense aRNA. The resultant aRNA was rigorously analyzed for possible introduced changes. DMSO was used as a cell preservative for frozen storage of urine samples. RESULTS Good quality aRNA was obtained for over 100 samples collected at two different institutions. The process of RNA amplification removed co‐isolated DNA in some samples, which did not affect RNA amplification. Amplification did not amplify genes that were absent and produce other expression alterations. The sense aRNA could be used to generate urinary transcriptomes specific to individual patients. No chaotropic agents for RNA preservation were added to the urine samples so that the supernatant could be used for analysis of secreted protein biomarkers. The time of donation was not important since patients were seen during the entire day. DMSO was an effective cell preservative for freezing urine. CONCLUSIONS Urinary RNA can be readily isolated and amplified for prostate cancer biomarker analysis. Individual patients had unique set of transcripts derived from their tumor. Prostate 75:1886–1895, 2015. © 2015 Wiley Periodicals, Inc.